2011
DOI: 10.1530/rep-11-0177
|View full text |Cite
|
Sign up to set email alerts
|

X-linked inhibitor of apoptosis protein and active caspase-3 expression patterns in antral follicles in the sheep ovary

Abstract: X-linked inhibitor of apoptosis protein (XIAP) interacts with caspases to inhibit their activity, thereby providing a potential mechanism for regulation of granulosa cell apoptosis occurring during follicular atresia. The aim of this study was to determine the presence and localization of XIAP mRNA and protein content in the sheep ovary and compare these expression patterns with active caspase-3 protein in the same antral follicles. Romney ewe estrous cycles (nZ25) were synchronized with 2-3 Estrumate injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…Moreover, subsequent studies in pigs and sheep have confirmed granulosa and thecal cell expression in antral follicles (Cheng et al 2008, Phillipps et al 2011. In sheep, XIAP has been detected at the protein level early in development in primary staged follicles up to large antral follicles (Phillipps et al 2011). This widespread expression across cell types and follicle stages suggests that XIAP and potentially IAPs in general are pivotal factors involved in regulating the dynamic environment within the ovary.…”
Section: Inhibitor Of Apoptosis Proteinsmentioning
confidence: 89%
See 4 more Smart Citations
“…Moreover, subsequent studies in pigs and sheep have confirmed granulosa and thecal cell expression in antral follicles (Cheng et al 2008, Phillipps et al 2011. In sheep, XIAP has been detected at the protein level early in development in primary staged follicles up to large antral follicles (Phillipps et al 2011). This widespread expression across cell types and follicle stages suggests that XIAP and potentially IAPs in general are pivotal factors involved in regulating the dynamic environment within the ovary.…”
Section: Inhibitor Of Apoptosis Proteinsmentioning
confidence: 89%
“…In rats, XIAP is present in granulosa cells, thecal tissue and oocytes within follicles from the preantral stage onwards (Li et al 1998). Moreover, subsequent studies in pigs and sheep have confirmed granulosa and thecal cell expression in antral follicles (Cheng et al 2008, Phillipps et al 2011. In sheep, XIAP has been detected at the protein level early in development in primary staged follicles up to large antral follicles (Phillipps et al 2011).…”
Section: Inhibitor Of Apoptosis Proteinsmentioning
confidence: 92%
See 3 more Smart Citations